Review of the Impact of Yogic Exercises on Motor, Physiological, and Psychological Variables in College-Aged Girls (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2026)
This review explores the impact of yogic exercises on the motor, physiological, and psychological variables in college-aged girls, a demographic that faces unique physical and mental health challenges. With the increasing integration of yoga into wellness programs, this review aims to synthesize existing research to better understand its benefits for young women. The review examines studies that assess various motor abilities such as flexibility, balance, and strength, alongside physiological parameters like cardiovascular health, respiratory function, and metabolic rate. Additionally, it evaluates the psychological impact of yoga, particularly in reducing stress, anxiety, and enhancing overall mental well-being. The collected evidence suggests that regular practice of yogic exercises significantly improves motor functions, optimizes physiological health, and positively influences psychological states. The findings indicate that yoga is an effective, holistic approach to enhancing both physical and mental health in college-aged girls, offering a viable strategy for managing the demands of academic and social life. This review underscores the importance of incorporating yoga into the daily routines of young women for comprehensive health benefits.